2012
DOI: 10.1111/j.1743-6109.2011.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction is Not a Mirror of Endothelial Dysfunction in HIV-Infected Patients

Abstract: Introduction The penis has been compared to a barometer of endothelial health, erectile dysfunction (ED) being an early sign of endothelial dysfunction. Aim The aim of the study was to investigate the extent of the association between ED and endothelial dysfunction in patients with human immunodeficiency virus (HIV) infection on antiretroviral therapy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 31 publications
6
33
2
Order By: Relevance
“…This is the first study comparing the prevalence of ED in HIV‐infected men and HIV‐uninfected men, and it demonstrates an increased prevalence of ED in men with the HIV infection. Hence, the results of the present study confirm initial results previously reported by this group and other authors [11–14,18,19].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is the first study comparing the prevalence of ED in HIV‐infected men and HIV‐uninfected men, and it demonstrates an increased prevalence of ED in men with the HIV infection. Hence, the results of the present study confirm initial results previously reported by this group and other authors [11–14,18,19].…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, the role of hypogonadism in causing ED is confirmed in this study but seems to be less pronounced than expected in the setting of HIV, as confirmed by previous studies [13,14,19]. Second, various psychological factors including the fear of HIV transmission and changes in body image may affect sexual desire [11,12,18]. Hence, sexual desire needs to be further investigated in the context of HIV by using much more precise tools for “desire.”…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In particular, erectile dysfunction (ED) is prevalent and has been reported to be present in between 9% and 74% of HIV-positive men [28]. In that study, Guaraldi et al [28] studied 133 HIV-positive men and found prevalence rates of ED of 55% and 65% of men aged less than or more than 50 years old, respectively. Comparison of TT and FT was made in those with and those without ED and no significant differences were observed.…”
Section: Androgens Sexual Function and Hivmentioning
confidence: 99%